(untitled) (Malay Literature, 2022)
The panji tales were popular in Java and gained widespread popularity throughout the Malay Archipelago at one point of time. Many manuscripts of these Panji tales have been studied using various approaches and research frameworks by both local and foreign researchers. However, there is still a dearth of the research, especially studies of the panji tales which were documented in Malaysia, despite the large number of manuscripts stored at the Malay Documentation Centre of Dewan Bahasa dan Pustaka, the National Library of Malaysia and the University of Malaya Library. Research related to the appearance of women character in the panji tales is still not thoroughly discussed by researchers, especially in helping readers to appreciate the beauty of the genre. Therefore, formalistic approach is used in this paper to examine the character’s appearance in the manuscript MS 46 panji tales entitled Hikayat Kelana Sita Kembara documented in the Malay Documentation Center, Dewan Bahasa dan Pustaka. The discussion in this paper aims (i) to identify women’s role of Ken Banjaransari in the panji tales of Hikayat Kelana Sita Kembara; (ii) to discuss the methods and techniques of writing used by the author to show the appearance of the women’s character of Ken Banjaransari; and (iii) to identify the effect of the role of women’s character of Ken Banjaransari on the work and readers of the panji tales Hikayat Kelana Sita Kembara. In conclusion, the appearance of a women’s character in panji tales Hikayat Kelana Sita Kembara successfully shows the ability of the author to use various writing techniques to build women’s character in order to produce an interesting story of the panji tales. Full text: PDF